ChemInform Abstract: Highly Facile and Regio‐Selective Synthesis of Pyrazolo[1, 5‐a]pyrimidines via Reactions of 1, 2‐Allenic Ketones with Aminopyrazoles. Issue 35 (2nd September 2014) - Zhang, Xinying; Song, Yunping; Gao, Lin; Guo, Xiaojie; Fan, Xuesen
Abstract The title reaction shows high regioselectivity with all the allenic ketones substrates (II), except for those bearing an alkyl group at the internal position of the allene moiety, e.g. (IV).